Răspuns :
Raspuns:
Explicație pas cu pas:
a)3x^2+6x ; 3x×(x+2) ; b)(4x-1)(x-3)+(4x-1)(2x+9) ; 3(4x-1)(x+2) ; c)nu merge rezolvat,dar cred ca ai dorit sa spui 3x^2+2v6x+2 deoarece la toate exercitiile ai pus x ; (xv3+v2)^2 ; d)(3x-1)^2-(3x-1)(x-3) ; 2(3x-1)(x+1)
v=radical
Răspuns:
Explicație pas cu pas:
3x^2 + 6x = 3x(x + 2)
___________
(4x-1)(x-3) + (4x-1)(2x+9) = (4x - 1)(x - 3 + 2x + 9) = (4x - 1)(3x + 6) =
= 3(4x - 1)(x + 2)
____________
3x^2 + 2√6x + 2 = (x√3+ √2)^2
______________
(3x - 1)^2 - (3x - 1)(x - 3) = (3x - 1)(3x - 1 - x + 3) = (3x - 1)(2x + 2) = 2(3x-1)(x+1)